Evaluation of selected biochemical parameters of a group of calves after colostrum intake - Güneş, Yazgülü; Akkaş, Mehmet Emin; Yıldırım, Kübra Nur; Kaçar, Yiğit; Kasap, Sevim; Evci, Fatma Zehra; Şentürk, Sezgin (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2025)
The aim of the presented study was to evaluate some selected biochemical values of a group of newborn Holstein calves after colostrum intake.Fifteen newborn Holstein calves of both sexes fed with high quality (Brix≥22%) colostrum were participated in our study. Blood samples were taken at birth (before colostrum intake) and after 24th hours of feeding with colostrum. Serum samples were analyzed with Reflotron Plus biochemistry device. Analysis results were evaluated at SigmaPlot statistical program.It was observed that gamma-glutamyl transferase (GGT), globulin (GLOB), total protein (TP), aspartate aminotransferase (AST), and total cholesterol (TCHOL) concentrations increased, albumin (ALB) concentration and albumin/globulin ratio (ALB/GLOB) decreased and calcium (Ca), magnesium (Mg), phosphorus (P), blood urea nitrogen (BUN) concentrations did not change after colostrum consumption.Although TP, GLOB and GGT levels are commonly used to determine passive immunity status in calves, changes in ALB, AST and TCHOL levels and ALB/GLOB may also be used to determine passive immune transfer in calves.
Keywords: Colostrum; neonatal calves; albumin; cholesterol; passive transfer immunity